An analytical study of the primary stage upgraded science textbooks in the light of basic science processes - Alotaibi, Mohammed Mofareh (Journal of Educational and Psychological Sciences, 2020)
The study aimed at Knowing the basic science processes included in the Science book and Activity book developer for fourth primary grade (the first semester and second semester), revised edition in 2011 year. The researcher used descriptive analytical method and prepared a list of basic science processes in which he adopted the classification of the American Association for Science development, which divided the basic science processes into eight key processes (observation, classification, measurement, communication, prediction, deduction, use of the relationship of place and time, use of numbers) and then tested the validity and reliability. The study showed a number of results, the most important was: That the basic science processes existed in different proportions in the Science and activity books, where the observation process comes in the first rank in comparative with the other the basic science processes. In light of the results of the study the researcher recommended the following: reviewing the order of priorities and processes ratios to each other in the light of the stage of cognitive development and in a way that realizes the balance and interdependence between the various science processes. , determining suitable standards that take into account the ages of the learners in designing curriculum, guiding curriculum designers to focus on the basic science processes.
Keywords: upgraded science textbooks; primary stage; basic science processes